Peningkatan hasil belajar luas bangun datar melalui pendekatan contextual teaching and learning (CTL) pada siswa Kelas III SDN 04 Lunang - Purwanto Purwanto (Indonesian Institute for Counseling, Education and Therapy (IICET), 2018)
Learning widespread flat on students SDN 04 Lunang District Lunang still conventional. Learning is still teacher-centered, so boring for students. For that researchers interested in improving the process of learning mathematics, especially learning square and rectangular area through the approach Contextual Teaching and Learning (CTL). CTL approach is felt able to overcome the existing problems. The approach used in this study is a qualitative approach. Research data in the form of information about process and data result of action obtained from the result of observation, test result, discussion and documentation. Researcher's subjects consisted of grade III students of SDN. 04 Lunang which amounted to 29 people. Data analysis was done by using the data analysis model. The research procedure is done through four stages: 1) planning 2) implementation 3) observation 4) reflection. The result of this research is CTL approach can improve the learning result of the wide area of wake up that is about the area of square and rectangle.